(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
To the new forms of conflict taking place in the world correspond, or are linked, new forms of power: from cognitive warfare to sharp power, up to what is now called surveillance capitalism. Through cognitive conflict and sharp power strategies, we are witnessing an epochal change, an IT revolution that brings political conflict into a digital dimension, which acts on the ground of public opinion, politics and economics; but even more subtly it acts in the control and conditioning of knowledge, of our world view and of facts. The general objective, from a political philosophy and communication ethics point of view, is to understand what changes are taking place and the purposes of controlling information, the conditioning of knowledge, the power of world markets and economic forces, which can be destructive as weapons of war: they can affect the strength of moral and collective resistance of a people, the reputation of a head of state, can pollute information for the failure of diplomatic operations, etc. How can one find adequate tools for cognitive response, autonomy of judgment and decision, exercise of freedom, protection of rights, in particular those of the most fragile social groups who are also the most affected by the new forms of power and unconventional conflict? The aim of my work will be to analyze forms, methods and languages of this interweaving of knowledge conditioning, digital market control, power (political and social), and global competitiveness